Jan Józef Szczepański’s Questions about the Meaning of Faith. Based on Dziennik (Journal) - Gontarz, Beata (Sensus Historiae, 2020)
The starting point for the author of the article is to recognize Jan Józef Szczepański’s Dziennik as a testimony of self-nurturing and self-education. The journal records show the processual quality of “designing” life by the author. The purpose of the article is to characterize the drama of inability to believe presented in the journal in the perspective of the philosophy of faith. The analysis of the writer’s attitude leads to the conclusion that his objection to temporality and nothingness is a confirmation of the meaning of faith, despite the inability to decide which Søren Kierkegaard called the “leap to faith”. The article also contains a reconstruction of Szczepański’s views on writing as the opposition to passing, which is his individual path to add meaning to his own life.